Evaluation of Drinking Water Needs in Wae Decer, Manggarai Regency, Nusa Tenggara Timur Province - Setyowati, Rr Diah Nugraheni; Junaidi, Rahmad; Suriani, Efa (Proceeding International Conference on Science and Engineering, 2019)
Drinking water is a basic need for humans. The provision of drinking water throughout Indonesia is an obligation that has been stated in UUD 45. Based on the Bappenas study with the Ministry of Public Works, universal access to drinking water is targeted to reach 84,8% nationally. Then, this universal access must increase to 92,2% in 2018. In the end, access to drinking water for the community in 2019 is 100%. Based on this description, every region in Indonesia must have universal access to proper drinking water. Manggarai Regency is one of the districts that will alleviate the problem of universal access to drinking water. Existing water sources in Manggarai Regency are in various locations of hills and mountains. This water source is a source of water that can be used as a source of drinking water. Based on the study of SPAM Master Plan, residents of Manggarai Regency who have had access to adequate drinking water are 57.61%. The percentage value is still below the threshold of decent MDGs in 2015 which is 68%. Considering that the target of fulfilling universal access to drinking water in 2019 is 100%, it is necessary to have a major breakthrough in drinking water supply in Manggarai Regency. One way that needs to be done is to evaluate the drinking water needs. Based on the results of a field survey, Manggarai District has the potential of drinking water sources of 150 Lps, water has been utilized by 30 Lps and the services to be developed are 40 Lps. The method used in this research is quantitative descriptive method. The results of the analysis obtained from the study on the evaluation of drinking water needs are long-term drinking water needs in 8 (eight villages), the capacity of clean water from Wae Decer water spring cannot supply drinking water by 2029. In 2028, the remaining clean water capacity from MA. Wae Decer only has 0.16 liters per second. If Wae Decer SPAM wants to be extended to 2037 according to long-term planning, then in 2018 the required supply capacity is 48,15 liters per second. The difference of 8,15 liters per second can be taken from Wae Decer which still has the remaining idle capacity of 77 liters per second in 2037. This capacity can be used for the development of drinking water reaching other villages that intersect with the DED Wae Decer system and or added from source of springs adjacent to Wae Decer clean water network.